PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, MOTIVASI DAN SISTEM PENILAIAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. POS INDONESIA (PERSERO) JAKARTA TIMUR - Mei; Siti Nurbaeti (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
This study aims to find out how much influence leadership style, compensation, motivation and work assessment system on employee job satisfaction on PT. Pos Indonesia (Persero) East Jakarta. Samples were taken by 50 employees using incidental sampling techniques. The results showed that partial leadership and motivation styles had a significant influence on employee job satisfaction, while partial compensation and work assessment system had an insignificant influence on the job satisfaction of PT employees. Pos Indonesia (Persero) East Jakarta. Simultaneously leadership style, compensation, motivation and work assessment system have a significant influence on the job satisfaction of PT employees. Pos Indonesia (Persero) East Jakarta. The magnitude of the influence of leadership style variables, compensation, motivation and simultaneous work assessment system on employee job satisfaction was 64.6%, while the remaining 35.4% was influenced by other variables not studied in this study.